Age of onset, treatment response, and survival rates in Dutch Kooiker dogs diagnosed with hereditary polymyositis - Opmeer, Yvet; Alf, Vanessa; Leegwater, Peter A. J.; Fieten, Hille; Mandigers, Paul J. J. (Frontiers in Veterinary Science, 2025)
IntroductionHereditary polymyositis in Kooiker dogs is genetically linked to the deletion of a 39 kb DNA fragment located 10 kb upstream of the interleukin IL21/IL2 locus, exhibiting low penetrance. This study aims to identify prognostic factors for Kooiker dogs that are affected and evaluate three treatments: (1) glucocorticoid monotherapy, (2) glucocorticoids combined with supplements (vitamin B, L-carnitine, and coenzyme Q10), and (3) glucocorticoids combined with supplements and oclacitinib.MethodThis study incorporates both retrospective and prospective designs. A total of 97 Kooiker dogs diagnosed with histopathologically confirmed polymyositis, or those showing clinical signs consistent with polymyositis and homozygous or heterozygous for a 39-kb deletion, were included. Dogs seen before the end of 2006 received only Treatment 1, those identified between 2007 and 2015 received Treatment 2, and those seen after 2015 received Treatment 3. A dataset was created that included sex, neuter status, age of onset (AoO), the 39 kb deletion, clinical signs, treatment, creatinine kinase (CK) activity at diagnosis and during follow-up visits, owner-reported improvement during treatment, cause of death, and date of death. Descriptive statistics and Cox proportional hazards survival analysis were conducted to examine factors influencing age of onset, treatment response, and survival.ResultsThe 39 kb deletion showed no association with clinical signs or creatine kinase (CK) activity at diagnosis. However, homozygous Kooiker dogs with the 39 kb deletion had a lower AoO. A significant decrease in CK activity was observed in 18 dogs during the first recheck after treatment, and most owners reported clinical improvement following the start of treatment. The type of treatment influenced survival time, with dogs treated with glucocorticoids, supplements, and oclacitinib having the longest survival.DiscussionA treatment regimen that included glucocorticoids, supplements, and oclacitinib was the most effective in this study, although it was not statistically significant.